2013
DOI: 10.2190/ec.48.3.c
|View full text |Cite
|
Sign up to set email alerts
|

Skills-O-Mat: Computer Supported Interactive Motion- and Game-Based Training in Mixing Alginate in Dental Education

Abstract: The training of motor skills is a crucial aspect of medical education today. Serious games and haptic virtual simulations have been used in the training of surgical procedures. Otherwise, however, a combination of serious games and motor skills training is rarely used in medical education. This article presents Skills-O-Mat, an interactive serious game for training rhythmic and period motor skills. In its first application the game supports dental students being trained in alginate mixing in a blended learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 26 publications
2
54
0
1
Order By: Relevance
“…Motivation is considered a central factor in the majority of reviewed studies (Felicia, 2011;Ljungkvist & Mozelius, 2012;von Wangenheim et al, 2012;Bellotti et al, 2013;Hannig et al, 2013;Ahmad et al, 2013;Pløhn, 2013;Denholm et al, 2012;Dzeng et al, 2014;Lancaster, 2014;Ariffin et al, 2014;Bolliger et al, 2015;Cózar-Gutiérrez, & Sáez-López, 2016;Dankbaar et al, 2016;Fu et al, 2016). Some results suggest the effectiveness of GBL in motivating and achieving learning goals can be found at the lower levels of Bloom's taxonomy (e.g.…”
Section: Motivation and Engagementmentioning
confidence: 99%
“…Motivation is considered a central factor in the majority of reviewed studies (Felicia, 2011;Ljungkvist & Mozelius, 2012;von Wangenheim et al, 2012;Bellotti et al, 2013;Hannig et al, 2013;Ahmad et al, 2013;Pløhn, 2013;Denholm et al, 2012;Dzeng et al, 2014;Lancaster, 2014;Ariffin et al, 2014;Bolliger et al, 2015;Cózar-Gutiérrez, & Sáez-López, 2016;Dankbaar et al, 2016;Fu et al, 2016). Some results suggest the effectiveness of GBL in motivating and achieving learning goals can be found at the lower levels of Bloom's taxonomy (e.g.…”
Section: Motivation and Engagementmentioning
confidence: 99%
“…The game requires only a training video and motion data as input, and is designed as a reusable component. The game is a valuable instrument for teaching and developing practical skills [26].…”
Section: Educational Games In Higher Educationmentioning
confidence: 99%
“…To a certain extent, the game can be tailored to meet the desired learning goals. Eight studies found clearly defined learning objectives in using a specific simulation or game to be an important enabling factor [32], [35], [37], [42], [43], [44], [45], [46]. For example, Castronovo et al [46] integrated the modeling simulation Virtual Construction Simulator 4 in a third year course 'Introduction to the Building Industry' and a fourth year course 'Building Construction Engineering' at Penn State University.…”
Section: Enabling and Constraining Factorsmentioning
confidence: 99%